2021
DOI: 10.3389/fcell.2021.624089
|View full text |Cite
|
Sign up to set email alerts
|

LUZP1 Controls Cell Division, Migration and Invasion Through Regulation of the Actin Cytoskeleton

Abstract: LUZP1 is a centrosomal and actin cytoskeleton-localizing protein that regulates both ciliogenesis and actin filament bundling. As the cytoskeleton and cilia are implicated in metastasis and tumor suppression, we examined roles for LUZP1 in the context of cancer. Here we show that LUZP1 exhibits frequent genomic aberrations in cancer, with a predominance of gene deletions. Furthermore, we demonstrate that CRISPR/Cas9-mediated loss of Luzp1 in mouse fibroblasts promotes cell migration and invasion features, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
14
2
Order By: Relevance
“…We performed network analysis using IPA on the list of differentially expressed proteins in both the diffuse and intestinal subtypes of gastric cancer. IPA network analysis of the diffuse subtype showed upregulation of proteins like HSPB1 [ 37 , 38 ], KCTD [ 39 , 40 , 41 , 42 ], TPM3 [ 43 , 44 , 45 , 46 ], PDLIM7 [ 47 , 48 , 49 ], LUZP1 [ 50 ], ACTN1 [ 51 , 52 ], and CFL2 [ 53 ], which have oncogenic properties in the topmost network ( Supplementary Figure S1 ). These proteins are involved in promoting tumor growth, invasion and resistance to anti-tumor therapy in various cancers including gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…We performed network analysis using IPA on the list of differentially expressed proteins in both the diffuse and intestinal subtypes of gastric cancer. IPA network analysis of the diffuse subtype showed upregulation of proteins like HSPB1 [ 37 , 38 ], KCTD [ 39 , 40 , 41 , 42 ], TPM3 [ 43 , 44 , 45 , 46 ], PDLIM7 [ 47 , 48 , 49 ], LUZP1 [ 50 ], ACTN1 [ 51 , 52 ], and CFL2 [ 53 ], which have oncogenic properties in the topmost network ( Supplementary Figure S1 ). These proteins are involved in promoting tumor growth, invasion and resistance to anti-tumor therapy in various cancers including gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…It remains unknown why cells have the unnecessary delay in contraction during cytokinesis via LUZP1. Recent studies have reported that LUZP1 expression is downregulated in several types of cancer and that LUZP1 can suppress the proliferation of some cancer cells (Dong et al, 2021; Bozal-Basterra et al, 2021). These findings suggest that LUZP1 may contribute to genome stability by preventing a failed chromosome distribution by delaying cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and location of protein activation and inactivation during cell division are highly regulated by post-translational modifications, such as protein phosphorylation and ubiquitination, to ensure the accurate progression of cell division (Lara- Gonzalez et al, 2021;Nasa et al, 2018;Vagnarelli, 2021). The chromosomal passenger complex (CPC) is an essential kinase complex for mitosis and is required for various mitotic events, such as chromosome condensation, kinetochore-microtubule attachment, spindle assembly checkpoint, cleavage furrow ingression, and abscission (Carmena et Salaun et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19503-1-AP, 1:100; Proteintech, Wuhan, China) ( 31 ) and TUBG1 (Cat No. 15176-1-AP, 1:100; Proteintech, Wuhan, China) ( 32 ). Two pathologists observed the results.…”
Section: Methodsmentioning
confidence: 99%